2017
DOI: 10.5423/rpd.2017.23.4.334
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Efficient Bioassay Method to Evaluate Resistance of Chili Pepper Cultivars to Ralstonia solanacearum

Abstract: Bacterial wilt caused by Ralstonia solanacearum is an important disease in cultivation of chili pepper, causing plant death and significant yield losses. Cultivation of disease-resistant varieties is the most suitable measure to control bacterial wilt of chili pepper. To establish an efficient screening method for resistant chili pepper to R. solanacearum, six resistant or susceptible cultivars to the R. solanacearum were selected and the development of bacterial wilt on the cultivars according to several cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
0
10
2
2
Order By: Relevance
“…The 'Gangryeokjosenggeon' (R), 'Meotjinsanai' (MR), 'PR-Daedeulbo' (S), and 'Supermanidda' (S) have the same traits in either inoculation method (Table 1). However, the traits of the root-drenching method in 'PR-Cheongyang', 'Ilsongjung', 'Muhanjilju', and PR-'Jangwongeubje' were MR or S phenotypes [15], but in this study represented all R phenotypes. 'Muhanjilju' and 'Meotjinsanai' also displayed previously different traits with S, MR, and R on infection methods and/or R. solanacearum strains [16], whereas we observed R and MR uniformly in each cultivar, respectively (Table 1 and Fig.…”
Section: Development Of An Efficient Evaluation System For Resistance To R Solanacearum In Peppercontrasting
confidence: 56%
See 4 more Smart Citations
“…The 'Gangryeokjosenggeon' (R), 'Meotjinsanai' (MR), 'PR-Daedeulbo' (S), and 'Supermanidda' (S) have the same traits in either inoculation method (Table 1). However, the traits of the root-drenching method in 'PR-Cheongyang', 'Ilsongjung', 'Muhanjilju', and PR-'Jangwongeubje' were MR or S phenotypes [15], but in this study represented all R phenotypes. 'Muhanjilju' and 'Meotjinsanai' also displayed previously different traits with S, MR, and R on infection methods and/or R. solanacearum strains [16], whereas we observed R and MR uniformly in each cultivar, respectively (Table 1 and Fig.…”
Section: Development Of An Efficient Evaluation System For Resistance To R Solanacearum In Peppercontrasting
confidence: 56%
“…1C). Collectively, these data indicated that 'MC4' also has a suitable resistance to leaf wilting disease by R. solaneacerum alongside BW disease through root infection [15].…”
Section: Identification Of Leaf Wilt Symptoms Between Resistant and Susceptible Peppermentioning
confidence: 81%
See 3 more Smart Citations